Intentional harmony: laying the groundwork for musical independence - Mills, Michael Jeffrey (Kansas State University, 2021)
In the lessons I present, my students worked toward developing and reinforcing their musical independence. For the purpose of this report, I define musical independence as the student’s ability to perform an independent line of music in various choral music textures. Although this skill is often developed at the elementary and middle school levels, I have found that many students entering my program lack the necessary skills and experience to succeed in singing traditional three and four-part choral music. Through a series of transformations over several lessons, students will change a simple melody into a multi-layered musical experience by utilizing different textures of harmony. These intentional uses of various textures over the course of their time in my program will help students find greater success in singing multi-part choral music. Some of these transformations will be explicitly dictated by me, while others provide students with the opportunity to compose or improvise within certain parameters. This focus on musical independence is one of several adjustments I have made to the curriculum I employ in my classroom as a result of my learning and experiences in the Kansas State Summer Master’s Program. The course objectives I utilized in my classroom had remained relatively the same over my first nine years of teaching. Now, as a direct result of my coursework at K State, I have found clearer ways to describe my objectives which has, in turn, clarified how best to assess my students. I have developed overall program objectives as well as individual course objectives which build from one course to the next. These changes have helped simplify classroom procedures and the planning process leading up to teaching from year to year. The primary driving force behind these changes lies in the influence and importance of personal philosophy. Up to this point in my career, I had not intentionally written out my philosophies as a music educator. Although I regularly thought about my beliefs regarding the many facets of my profession, the process of writing them out has brought added clarity and focus to what matters most in my curriculum. Moreover, the ability to justify my philosophies with credible sources has brought greater depth to my core beliefs. In essence, the process of writing out my philosophy regarding music education has helped me to return to my core, authentic self as a musician. This re-centering of identity has shed light on things which did not serve a purpose in my classroom and helped me identify practices better suited to reach my objectives.
Keywords: Music; Choir; Musical independence; Harmony; Singing